The impact of supplementation with highland barley in different nutrients on weight loss: The nutrients and function relationship - Fan Xie; Yuting Yan; Xin Gao; Haocheng She; Jingyi Wang; Jie Li; Yi Zhang; Jun Zhang; Zhou Zhang; Lianzhong Ai (Food Chemistry: X)
The dietary fiber in highland barley (HB) may be a key nutrient in exerting its physiological functions. How about the effects of other nutrients? In this study, a high-fat diet (HFD)-induced obese mice was constructed to investigate the effects of HB in different nutrients on weight loss. The results showed that peeling treatment had varying effects on HB nutrients. Consumption of HB significantly mitigated weight gain, postprandial blood glucose levels, organ weight, adipose tissue weight, and fat accumulation in obese mice. Consumption of HB also ameliorated hepatic steatosis, hyperlipemia, abnormal liver function, and dysregulation of inflammatory factor expression in mice. Unpeeled and once peeled HB presented the best effect. Furthermore, HB consumption improved the imbalance of gut microbiota in HFD-induced mice, with protein and dietary fiber being the key factors in exerting the improvement effect. This study highlights the potential of protein and dietary fiber in HB for treating obesity.